Hannah Peace’s Suicide in Toni Morrison’s Sula: A Psychoanalytic Approach - Nindy Andini; Nur Saktiningrum (Lexicon, 2020)
This research discusses Hannah Peace’s suicide by exploring her past life, from her childhood until she decides to commit suicide. This research aims to find core issues faced by her and what triggers her to commit suicide. Psychoanalysis theories and theory of suicide proposed by Shneidman are applied in this research. The results show that her suicide is caused by psychological pain which stems from many painful experiences in her past life. After exploring her distressing experiences, it can be said that Hannah faces two core issues, which are fear of abandonment and fear of intimacy. However, her suicide is not merely caused by psychological pain. There are two factors which lead to her suicide: intrapsychic and interpersonal factors. Intrapsychic factor refers to the internal psychological processes of an individual, while interpersonal factor refers to the relationship between an individual and other people.